Genome-wide identification of the bZIP transcription factor family and expression analysis under abiotic stress in Zanthoxylum bungeanum - Changming Liu; Zhiguo Tian; Feng Xian (PLoS ONE, 2025)
Zanthoxylum bungeanum (Zb) is an economically and medicinally significant crop that faces numerous environmental stresses due to its broad distribution. Basic leucine zipper (bZIP) transcription factors are extensively involved in plant responses to abiotic stresses and play essential roles in these processes. However, the understanding of bZIP transcription factors in Zb remains limited. In this study, 275 ZbbZIPs, which are unevenly distributed across 50 chromosomes and are classified into 13 subfamilies. Each subfamily presents conserved gene structures and motifs. Whole-genome duplication (WGD) and segmental replication events have driven the expansion of ZbbZIPs. The ZbbZIP family contains a significant number of elements associated with stress and abscisic acid (ABA) responses, particularly in subfamily A. The codon usage pattern reveals a strong preference for T terminal codons in the ZbbZIP family. Compared with their expression levels under salt stress, the expression levels of the ZbbZIP family were greater under drought and cold stress. Homology annotation and expression profile analyses indicated that EVM0033673.1 (H, HYH), EVM0081289.1 (A, DPBF), EVM0001090.1 (A, DPBF), and EVM0023876.1 (A, ABF) may significantly contribute to Zb’s response to abiotic stresses. These results increase the understanding of the bZIP family and establish a basis for further investigations into the mechanisms by which Zb responds to abiotic stress.